Interkingdom Cross-Talk in Times of Stress: Salmonella Typhimurium Grown in the Presence of Catecholamines Inhibits Porcine Immune Functionality in vitro - Reiske, Lena; Schmucker, Sonja S.; Steuber, Julia; Toulouse, Charlotte; Pfaffinger, Birgit; Stefanski, Volker (Frontiers in Immunology, 2020)
In stressful situations, catecholamines modulate mammalian immune function and, in addition, they can be sensed by many bacteria. Catecholamine sensing was also found in the zoonotic gut pathogen Salmonella Typhimurium, probably contributing to the stress-induced increased risk of salmonellosis. Virulence traits like proliferation and invasiveness are promoted upon bacterial catecholamine sensing but it is unknown whether S. Typhimurium may also inhibit mammalian immune function in stressful situations. We thus investigated whether supernatants from S. Typhimurium grown in the presence of catecholamines modulate porcine mitogen-induced lymphocyte proliferation. Lymphocyte proliferation was reduced by supernatants from catecholamine-exposed Salmonella in a dose-dependent manner. We further examined whether adrenaline oxidation to adrenochrome, which is promoted by bacteria, could be responsible for the observed effect but this molecule either enhanced lymphocyte functionality or had no effect. We could thereby exclude adrenochrome as a potential immunomodulating agent produced by S. Typhimurium. This study is the first to demonstrate that bacteria grown in the presence of catecholamine stress hormones alter their growth environment, probably by producing immunomodulating substances, in a way that host immune response is suppressed. These findings add a new dimension to interkingdom signalling and provide novel clues to explain the increased susceptibility of a stressed host to Salmonella infection.